Islamic Banking Revolution In Malaysia: A Review - Fam, Soo Fen; Saleh, Ali Husseini; Ahmat, Norun Najjah; Azmi, Fadhlur Rahim; Prastyo, Dedy Dwi; Yanto, Heri (Gyandhara International Academic Publications, 2019)
Purpose of the study: The study aims to review the development of Malaysian Islamic banks from the year 2008 to 2015 and its role in financing Malaysian economy. Methodology: The sources of data were collected from Malaysian banks, the reviews of the experience of Islamic banks in Malaysia has been discussed, then this study analysed the roles of Islamic banks in the allocation of resources in the banking system. finally, this study explained the overall development of performance in Islamic banks in Malaysia. Main Findings and Novelty: The results of this study show that the Malaysian Islamic banks have contributed on the structure of the Malaysian economy; particularly in supporting the SME (small and medium entrepreneurship) industries as well the large projects, which create a good positive impact on Malaysian economy and became one of the main financial sources of Malaysian investment. Applications of this study: Achieving the required requirements for the success of the desired Islamic financial system such as adherence to ethical controls and behavior would reduce the problematic ethical risks and the risks of information asymmetry and emphasis on the importance of participation in the banking system and the need to adopt them. © 2019 Gyandhara International Academic Publications.